Effects of training for two ball games on the saliva response of adrenocortical hormones to exercise in elite sportswomen - Filaire, E.; Duche, P.; Lac, G. (European Journal of Applied Physiology, 1998)
In a group of 20 elite female handball or volleyball players, an evaluation was made of the response to a 4-month training period of cortisol, androstenedione and dehydroepiandrosterone in the saliva. The regulators of these hormones during a period of exercise and during the course of a training programme would seem to be different.